An Anatomy of Autonomy: Managing Professionals - Joseph A. Raelin (Academy of Management Perspectives, 1989)
The most vexing problem in the management of salaried professionals is how to provide them with their espoused right of autonomy while ensuring adequate control of the organization. In this article, Joseph Raelin explains how a standard approach of granting professionals operational autonomy (autonomy over the means or procedures to be used) while according management administrative and strategic autonomy (autonomy over the activities of the organizational unit or over the missions of the entire enterprise) is a convenient norm for executives to adopt in most situations. However, he goes on to illustrate how to manage the critical exceptions: those conditions when professionals out to be granted administrative and strategic autonomy as well as those conditions when management may actually invade the operational autonomy of the professional.
Keywords: J24; J44; L84; M12; M51; O15; 330; Managing professionals; Professional autonomy; Managerial control; Professionalization